2021
DOI: 10.1002/ajoc.202100592
|View full text |Cite
|
Sign up to set email alerts
|

A N‐Heterocyclic Carbene‐Palladacycle with Constrained Aliphatic Linker: Synthesis, Characterization and Its Catalytic Application towards Suzuki‐Miyaura Cross‐Coupling

Abstract: The Suzuki-Miyaura coupling of various (hetero) aryl chlorides with aryl boronic acids was accomplished by N-heterocyclic carbene-palladacycles (NHCÀ Pd cycle ) in the aqueous phase. Intriguingly, the NHCÀ Pd cycle with a constrained aliphatic linker between the NHC ligand and the palladacycle moieties exhibited higher catalytic efficiency than the one without constrained linker under the identical reaction conditions, due to the fixed spatial structure around the metal catalytic center. The present outcome ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Therefore, researchers have focused on this interesting field of palladacycles and intensively explored their potential applications [12,30]. Today, many examples of palladacycles exist that show high catalytic activity in Suzuki-Miyaura [31][32][33][34][35][36][37][38][39][40][41][42], Sonogashira [41][42][43], Heck [44][45][46], Buchwald-Hartwig [47][48][49][50] coupling reactions, and carbonylation reactions [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have focused on this interesting field of palladacycles and intensively explored their potential applications [12,30]. Today, many examples of palladacycles exist that show high catalytic activity in Suzuki-Miyaura [31][32][33][34][35][36][37][38][39][40][41][42], Sonogashira [41][42][43], Heck [44][45][46], Buchwald-Hartwig [47][48][49][50] coupling reactions, and carbonylation reactions [51][52][53][54][55].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we found that the NHCÀ Pd cycle with a constrained aliphatic linker between NHC ligand and palladacycle moiety has higher catalytic efficiency than those without a constrained linker. [12] Thus, we proposed the fabrication of the core-shell magnetic mesoporous microspheres immobilized Nheterocyclic carbene-palladacycles catalyst with constrained aliphatic linkers (Fe 3 O 4 @mSiO 2 @NHCÀ Pd), achieving high catalyst loading, outstanding catalytic activity and multiple reusability without a significant decrease in catalytic performance even after 12 cycles for the Suzuki-Miyaura cross-coupling reaction of aryl chlorides and aryl boronic acids.…”
Section: Introductionmentioning
confidence: 99%